Dimensions of health workforce performance: a scoping review - Gianluca Fabiano; Juana Paola Bustamante; Laurence Codjia; Amani Siyam; Pascal Zurn (Global Labor Organization (GLO), 2024)
Introduction: The World Health Report 2006 defined 'availability', 'competence', 'responsiveness' and 'productivity' as the key dimensions of the health workforce (HWF) performance framework. Since then, new goals have been set to address population health needs by optimizing HWF performance and quality. The aim of this scoping review is to identify aspects of HWF performance dimensions that have emerged since the 2006 publication. Methods: A scoping review of the literature was performed to establish the knowledge base on HWF performance via the latest available evidence. The web search was conducted on the Science and MEDLINE databases, with Scholar citations from the World Health Report 2006. Results: The literature reveals new thematic areas in HWF performance that were not explicit in the 2006 framework, eg the role of retention and recruitment policies on HWF availability and broadening competence by incorporating HW cultural background, attitudes and values alongside technical skills. Concepts related to HWF responsiveness have expanded to include job quality and work environment. A shift in productivity emphasises the role of technologies in enhancing clinical practice and overall system efficiency. Last, recurring aspects of performance were related to pay schemes and such contextual factors as the role of communities and regulatory frameworks. Conclusions: This review lays the groundwork for a revised perspective on HWF performance, transitioning from separate dimensions to a more integrated approach. It highlights the importance of expanding the availability dimension to emphasise the role of personal and career development and alignment with individual values. Knowledge, technical skills, attitudes, behaviours, beliefs and cultural background all influence competence. Responsiveness is seen through a lens valuing health worker well-being. Conceptually, productivity is broadened to reflect a more nuanced understanding of efficiency, recognizing the role of technology, how work environment and teams impact performance, and the significance of remuneration, including financial and non-financial incentives and other contextual factors.
Additional information: Supplementary material A: https://www.econstor.eu/bitstream/10419/303149/2/GLO-DP-1492_Supplementary-material_A.pdf *** Supplementary material B: https://www.econstor.eu/bitstream/10419/303149/3/GLO-DP-1492_Supplementary-material_B.pdf
Keywords: I18; J08; J24; J24; 330; performance; productivity; retention; health workforce; health